Giant isolated transcranial Rosai-Dorfman disease with diffuse involvement of nasal and paranasal tissues: case report and literature review. (4th May 2019) - Zhong, Zhihong; Fu, Wei; Sun, Yuhao; Sun, Qingfang; Bian, Liuguan
Abstract: Rosai-Dorfman disease (RDD) is an uncommon systemic histioproliferative disease process characterized by sinus histiocytosis with massive lymphadenopathy, and isolated transcranial RDD (ITRDD) is extremely rare. We report a patient with giant ITRDD with diffuse involvement of nasal and paranasal tissues, showing favorable response to postoperative steroid therapy .